ASSESSMENT OF WHEAT GENOTYPES FOR THEIR LOW NITROGEN USE EFFICIENCY UNDER SEMI-ARID CONDITIONS OF PUNJAB, PAKISTAN - QAMAR , MJ; QAZI , MA; TARIQ, M; JAWAD, H; SHABIR, MA; ARIF, M; FAROOQ , MR; IQBAL, MN; HAFEEZ, Z; BASHIR , MA; JAMIL, S; BASHIR, F; et al. (Biological and Clinical Sciences Research Journal, 2024)
Nitrogen is one of the most important and critical macronutrients needed by plants for their optimal growth and development. The current experimental study was designed to examine the response of wheat variety Akbar-2019 under different nitrogen levels keeping the levels of phosphorus and potassium constant. The study was conducted in Chak No. 169/7.R Fort Abbas, District Bahawalnagar under the supervision of the Department of Soil Fertility (Field) during the crop year 2022-23. The experimental material was comprised of a wheat variety Akbar-2019 and five different treatments of nitrogen consisted of (i) N = 160 kg ha-1 (ii) N = 145 kg ha-1 (iii) N = 131 kg ha-1 (iv) N = 117 kg ha-1 and (v) N = 103 kg ha-1. The experiment was laid out under a randomized complete block design with three replications and 170 m² net plot size par treatment per replication. The results revealed the presence of highly significant variations among nitrogen treatments in wheat variety based on the agronomic and morpho-physiological parameters including flag leaf area, thousand-grain weight, grains per spike, relative water contents, stomatal conductance, net photosynthetic rate, biological yield and gain yield. Furthermore, the results also unveiled that treatments with higher nitrogen dosage produce better results for almost all the study parameters including grain yield. These results were also confirmed through correlation coefficient analysis and bar graph graphical representation based on mean data, where correlation coefficient analysis showed a strong positive correlation of grain yield with studied plant traits except biological yield for which the correlation was positive but non-significant. The results suggest that nitrogen in higher amounts up to a certain level is necessary for obtaining maximum output from wheat crops under semi-arid conditions.